Pemberdayaan Masyarakat Korban Letusan Gunung Semeru Melalui Program Aksi Solidaritas Kemanusiaan di Kabupaten Lumajang - Hosaini, Hosaini; Waziroh , Iro; Heryandi , M. Tubi; Muzayyanah, Muzayyanah; Safitri, Muharofah Nur (Proceedings of Annual Conference on Community Engagement, 2022)
The geographical location of this volcano is in two urban areas, Malang and Lumajang. This service analyzes the needs of the Semeru community after the burst of Mount Semeru, Lumajang Regency, both from the psychological aspect and the aspect of economic needs. Method The method used is participatory action research using a rapid rural appraisal (RRA) approach and a participatory rural appraisal (PRA) approach. Can ease the burden on the community of victims of the eruption of Mount Semeru b. people receive education in dealing with with various life problems so that they are not depressed c. People are driven and inspired to rise to organize a brighter life. Conclusion Humanitarian solidarity action program is important to be carried out as a form of implementing empathy and sympathy for the wider community, especially the people who need to solve various problems they face. The solidarity action programs carried out from the psychological aspect are a. educate people who experience depression through a spiritual approach b. assist in logistics and cash to ease the burden suffered by the victims of the Mount Semeru eruption.